Evi1 involved in benzene-induced haematotoxicity via modulation of PI3K/mTOR pathway and negative regulation Serpinb2. (25th February 2022) - Sun, Rongli; Yu, Linling; Xu, Kai; Pu, Yunqiu; Huang, Jiawei; Liu, Manman; Zhang, Juan; Yin, Lihong; Pu, Yuepu
Abstract: Benzene is a widely used chemical and an environmental pollutant. Exposure to benzene can cause blood diseases, but the mechanisms underlying benzene haematotoxicity have not been fully clarified. Ecotropic virus integration site-1 (Evi1), a transcription factor, plays important roles in normal haematopoiesis and haematological diseases. In this study, we investigated the role and mechanism of Evi1 in benzene-induced haematotoxicity. We found that benzene exposure significantly increased Evi1 level in white blood cells (WBCs) in occupational benzene workers as well as mouse bone marrow cells. Further in vitro results demonstrated that compared with control cells exposed to same 1, 4-benzoquinone (1, 4-BQ, an important active metabolite of benzene) concentration, Evi1 downregulation significantly reduced cell proliferation, and disrupted cell viability, apoptosis, erythroid and megakaryotic cell differentiation and cell cycle. Additionally, down-regulation of Evi1 suppressed phosphoinositide 3-kinase (PI3K)/mTOR signalling pathway and elevated its target gene Serpinb2 following 1, 4-BQ exposure. Moreover, the PI3K activator could partially relieve the inhibitory effect of down-regulation of Evi1 on cell proliferation and increase cell arrest in in G2/M phase. What's more, downregulation of Serpinb2 could partially alleviate proliferation inhibition and reverse cell cycle changes in G0/G1 phase and S phase induced by Evi1 inhibition. In conclusion, our data revealed that Evi1 downregulation aggravated the inhibition of cell proliferation and arrested cells in the G0/G1 phase when exposed to 1, 4-BQ, potentially by inactivating the PI3K/mTOR pathway and upregulating downstream target gene Serpinb2. Our study provides novel insights on mechanism by which Evi1 participates in benzene-induced haematotoxicity. Graphical abstract: Image 1 Highlights: Benzene exposure increased Evi1 in WBCs of workers and mouse BM cells. Evi1 influences 1, 4-benzoquinone-induced cytotoxicity in K562 cells. Evi1 involved in benzene haematotoxicity via regulation PI3K/mTOR and Serpinb2.